The influence of age on the responses of serum visfatin and insulin resistance to a single session of endurance exercise - هیوا رحمانی; سجاد احمدی زاد; مینو باسامی; مهدی هدایتی (فیزیولوژی ورزش و فعالیت بدنی)
Purpose: The purpose of this study was to investigate the effects of age on the responses of serum visfatin and insulin resistance index to a single session of endurance exercise. Methods: For this reason, 45 male subjects were allocated to three age groups (n=15) of young (20-30 уг, ВМІ:22.9), middle-aged (40-50 yr, BMI:25.9) and old (60-70 yr, ВМІ:26.4). After determining the maximal oxygen consumption (Vo,max), all subjects performed an exercise trial in a separate session encompassed performing 30 minutes of cycling at 60% of Vo₂max which was followed by 30 minutes of passive recovery. Before exercise, immediately after and at the end of 30 minutes recovery three blood samples were taken and were analyzed for determining the glucose, insulin, IL-6 and visfatin concentrations. Insulin resistance index was calculated using the glucose and insulin concentrations. To determine the effects of age on responses of all parameters to exercise and recovery, one way independent ANOVA was used. Results: Data analysis revealed that responses of visfatin to endurance exercise was affected by age (P<0.001). However, effects of age on responses of glucose, insulin, IL-6 and insulin resistance index were not significant (P>0.05). Irrespective of age, a single session of endurance exercise induced significant (P<0.05) changes in all parameters except for IL-6. Conclusion: It could be concluded that age is an effective factor on responses of visfatin to acute endurance exercise and that visfatin has no effect on reductions in insulin resistance index but it might be more an effective factor for energy balance through other pathways.